Nanoparticle Distribution in Three‐Layer Polymer–Nanoparticle Composite Films: Comparison of Experiment and Theory. (5th August 2014) - Bunk, Juliane K. G.; Drechsler, Astrid; Friedel, Peter; Rauch, Sebastian; Uhlmann, Petra; Stamm, Manfred; Rennekamp, Reinhold
<x xml:space="preserve">Abstract</x> The distribution of hydrophobic nanoparticles deposited on a hydrophilic polymer film is investigated by scanning electron microscopy, transmission electron microscopy, and atomic force microscopy before and after spin‐coating a polymer solution on the particle film and drying it at room temperature. Various polymers and solvents are used. To reach equilibrium, all investigated systems are annealed additionally above the glass transition temperature (Tg) of the polymers. The compatibility of the interacting components is estimated by calculating their surface energy, solubility, and mutual interaction parameters. The experimental results show a redistribution of the particles on both interfaces of the polymer film. This corresponds to the calculated immiscibility of particles and polymers. The distribution of the nanoparticles at the interfaces is related mainly to the vapor pressure of the solvent, that is, kinetic effects during spin‐coating. Only minor contributions result from surface energy, solubility, and interaction parameters.